Implementasi Pendidikan Kecakapan Hidup Multimedia Di Pkbm Bakti Indonesia - Pratama Indra Saputra; Muarifuddin Muarifuddin (Journal on Education, 2025)
Changes in the world of work from time to time must always be followed by the development of education. The development of education can essentially meet the expectations of the world of work as a provider of labor that has good knowledge, skills and personality. Meanwhile, education graduates are expected to be able to fill available job opportunities with their abilities. This condition is very different from what exists in the field. PKBM Bakti Indonesia is present to develop the potential of learning citizens by providing knowledge and skills of life skills education as well as developing attitudes and skills that they can apply in future life with mastery of multimedia technology. This research design uses descriptive qualitative which means to describe events or events that are happening. The problems in this study were formulated more specifically in order to focus on the research objectives. The results of the study when viewed with the CIPOO (Context, Input, Process, Output, Outcome) approach show that it has been running well, this is indicated by an increase in program graduates who are directly employed. PKBM Bakti Indonesia succeeded in developing the potential of graduates by providing knowledge and skills of life skills education and attitude development. PKBM Bakti Indonesia is a non-formal education institution that has a multimedia life skills program that directly graduates quality graduates who are independent and competitive.